Pesticide Utilization and Insecticide Residue Levels in Rice from Banaybanay, Davao Oriental - Edito Sumile; Lourdes Generalao (Davao Research Journal)
Pesticides for rice production were widely used in Banaybanay, Davao Oriental. These included insecticides, herbicide and molluscide in this order. etofenprox and fipronid were the most utilized insecticide, butachlor and thiobencarb+24D for herbicide. copper oxychloride and benomyl were the most used fungicides by farmers while niclosanide for mulluscide. Farmers used the conventional knapsack sprayer in applying pesticides in the rice field. Farmers usually applied insecticide at a range of one to more than 11 times but most applied it from one to five times. Herbicides and fungicides were applied once or twice per season although few had to apply five times Farmers' frequency of spraying and dosage of applying pesticides were usually based on the recommendation indicated on the product label. Only a few did not follow the manufacturer's instructions. Insecticide and herbicide were applied at a range of one to IOL; one to six L. of fungicide or molusscide; others had used one to 10 sachsets, and five to 50 sacks of fertilizer per cropping season. Twenty-two percent had been using pesticides for six to 10 years, and 4% for more than 31 years. Insesticide residues were detected in Hybrid rice. Cypermethrin residue was detected above the level of Allowable Daily Intake while deltamethrin was below it.